Flexible operation in the digital economy - Radović-Marković Mirjana; Vučeković Miloš; Marković Dušan (Trendovi u Poslovanju)
With the digitalization of companies and work, the business environment and working conditions have changed. Namely, the progress in ICT changed the ways of work organization and influenced the new work model. Teleworking and mobile work provided workers with the opportunity to adapt their time and place of work to their needs. Accordingly, digitization enables more complex organizational forms and affects an increasing number of tasks. The main goal of our study was to investigate the implications of work flexibility on the worker's health. In other words, are there any risks that this new working arrangement will lead to a shortening of working life? Our research has shown that these types of work arrangements can lead to increased workload and overwork, even where workers have a high level of autonomy. Consequently, workers are exposed to great health risks: stress, anxiety and other health problems related to the new work environment.